Phytic acid pre-modulated and Fe/N co-doped biochar derived from ramie fiber to active persulfate for efficient degradation of tetracycline via radical and non-radical pathways - Deng, Yuwei; Xiao, Lixi; Zhou, Huo; Cui, Boyan; Zhang, Lexin; Chen, Dongxinyu; Gu, Chenghui; Zhan, Ziyi; Wang, Rongling; Mei, Shou; Pei, Xuanyuan; Li, Qiang; et al. (Separation and purification technology, 2024)
•Ramie fiber was chosen as the carbon substrate for biochar production.•PA modified ramie fiber biochar provide loading sites for Fe and N.•TCH was eliminated by radical and non-radical pathways in the Fe/N-PABC/PDS system.•Fe/N-PABC/PDS* mediate TCH degradation through electron transfer.•DFT calculations reveal synergies among PABC, Fe, and N in TCH degradation. Biochar-driven advanced oxidation processes (AOPs) have been widely applied in water decontamination from recalcitrant organic pollutants, yet its performance is restricted due to the complex functional groups of precursors and the obstacles of regulating the active sites. Herein, we prepared a phytic acid (PA) pre-modulated and Fe/N co-doped biochar derived from ramie fiber (Fe/N-PABC) to activate peroxydisulfate (PDS) for tetracycline hydrochloride (TCH) removal. The pre-treatment by PA facilitates the formation of pore structure and provide abundant loading sites for subsequent iron and nitrogen (Fe, N) doping. The main forms of Fe, N present in Fe/N-PABC are Fe0, Fe (II), pyridine N, and graphite N, respectively. In the presence of Fe/N-PABC, 80 % of TCH were degraded by PDS in 20 min at pH 5.0, whereas only 16.3 % of TCH was removed by single PDS. The oxidation of TCH was affected in the presence of Cl-, NO3–, SO42-, H2PO4- and HCO3–. Meanwhile, the performance was also validated in authentic waters in terms of degradation efficiency of TCH. The synergistic effects of radical and 1O2 dominated non-radical pathways were confirmed with the introduction of Fe, N in the system. Electrochemical oxidation experiments and density functional theory (DFT) calculations unveiled the electron transfer pathway and the key role of Fe/N-PABC/PDS* as an intermediate oxide. The possible degradation pathways were proposed based on the identification of degradation products. This study sheds light on the innovative concepts for modulating functional biochar and offering fundamental mechanisms of antibiotic degradation in wastewater treatment.